2019
DOI: 10.3390/f10121087
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Evaluation of Stable Reference Genes for Quantitative Real-Time Polymerase Chain Reaction (qRT-PCR) Analysis in Chinese Fir Roots under Water, Phosphorus, and Nitrogen Stresses

Abstract: Chinese fir (Cunninghamia lanceolata) is an economical important timber species widely planted in southeastern Asia. Decline in yield and productivity during successive rotation is believed to be linked with abiotic stress, such as drought stress and nitrogen (N) and phosphorus (P) starvation. Molecular breeding could be an option to develop tolerant genotypes. For gene expression studies using quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR), stable reference genes are needed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…The amplification program was 95 °C for 3 min followed by 40 cycles of 95 °C for 20 s, 60 °C for 30 s, and 72 °C for 30 s. The specificity of the amplification was controlled by melting curve analysis (from 65 to 95 °C). We used β-Actin1(Forward: 5′- CTCTCTCAGCACCTTCGAGCAG − 3′, Reverse: 5′- TCCACATACAACCGCTCCACTG − 3′) as a reference gene to normalize expression level [ 10 ]. The relative expression of genes in different Pi treatments over time was calculated by 2 −ΔΔCt method.…”
Section: Methodsmentioning
confidence: 99%
“…The amplification program was 95 °C for 3 min followed by 40 cycles of 95 °C for 20 s, 60 °C for 30 s, and 72 °C for 30 s. The specificity of the amplification was controlled by melting curve analysis (from 65 to 95 °C). We used β-Actin1(Forward: 5′- CTCTCTCAGCACCTTCGAGCAG − 3′, Reverse: 5′- TCCACATACAACCGCTCCACTG − 3′) as a reference gene to normalize expression level [ 10 ]. The relative expression of genes in different Pi treatments over time was calculated by 2 −ΔΔCt method.…”
Section: Methodsmentioning
confidence: 99%
“…Since different statistical algorithms were applied, these differences in screening of optimal internal reference genes were acceptable. Finally, the RefFinder algorithm was used to comprehensively compare and rank these reference genes [33], suggesting that UBQ was the best reference gene in different tissues and growth of leaves, and IDH and PLA were the optimum references for gene expression normalization during the growth of corms and leafstalks, respectively. Based on the results that mentioned above, it is concluded that UBQ is the most suitable reference gene in arrowhead tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR was performed and analyzed using GoTag qPCR Master Mix (Promega) and a StepOnePlus™ real-time fluorescence quantitative PCR instrument (Corbett Research, Australia). β-Actin1 was used as a reference gene to normalize expression data, as this gene was found to be stable [35]. The primers for amplifying β-Actin1 were 5 -CTCTCTCAGCACCTTCGAGCAG-3 (Forward) and 5 -TCCACATACAACCGCTCCACTG-3 (Reverse).…”
Section: Expression Of the Clphr1 Gene In Roots Stems And Leaves Of mentioning
confidence: 99%